2018
DOI: 10.1002/app.47088
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking behaviors and mechanical properties of curable PDMS and PEG films with various contents of glycidyl methacrylate

Abstract: The real-time curing behaviors and surface mechanical properties of two curable systems, polydimethylsiloxane (PDMS) and poly(ethylene glycol) (PEG) films containing different portions of glycidyl methacrylate (GMA), were investigated via various measurements for potential application as anti-fouling coatings. In these mixtures, methacryloxypropyl-terminated PDMS and poly(ethylene glycol)dimethacrylate were used as the difunctional crosslinkers, and GMA was employed as the epoxy component. During the coating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In addition, Browning et al [19] enhanced the crosslinked network by adding a four-arm PEG acrylate crosslinker to linear PEGDA hydrogels of different molecular weights. Although it is well known that the degree of crosslinking can be altered by the formulation of a hydrogel, few studies have attempted to control the hydrogel network through changes in the crosslinking process [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Browning et al [19] enhanced the crosslinked network by adding a four-arm PEG acrylate crosslinker to linear PEGDA hydrogels of different molecular weights. Although it is well known that the degree of crosslinking can be altered by the formulation of a hydrogel, few studies have attempted to control the hydrogel network through changes in the crosslinking process [20].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ethylene glycol) dimethacrylate (PEGDMA, Mw = 550 g/mol) and glycidyl methacrylate (GMA, Mw = 142.15 g/mol) were used as a crosslinker and a monomer, respectively. Based on previous studies [16], the molar ratio for PEGDMA and GMA was fixed at 70:30 mol% (PEG-GMA30) in this study, to exclusively emphasize the role of epoxy groups in G-SiNPs. For the radical polymerization process performed via UV irradiation, 2,2-dimethoxy-2-phenylacetophenone (DMPA) was slightly inserted into the hydrogel mixtures (approximately 1 wt% based on the total weights of PEGDMA and GMA) To verify the formation of the G-SiNPs, the chemical changes at the surfaces of the Si-NPs and G-SiNPs were monitored via the attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FT-IR, Agilent Technology, Santa Clara, CA, USA) in transmittance mode.…”
Section: Formulation Of Uv Curable Hydrogel Mixturesmentioning
confidence: 99%
“…Furthermore, an epoxy unit on the film surface can be changed into hydrophobic or hydrophilic brushes in amphiphilic coating fields [ 15 ]. Kim et al [ 16 ] investigated the effect of glycidyl methacrylate (GMA) with an epoxy group on the chemo-rheological behaviors of PEG-based hydrogel mixtures. It was observed that a proper portion of GMA contributed to the formation of densely crosslinked networks in PEG hydrogel films, exhibiting enhanced rheological and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphiphilic block copolymers may be exploited to prevent dye transfer to the fabric surface in a manner analogous to anti-fouling systems used for marine paints. [31][32][33] The hydrophobic component of the block copolymer may be designed to adhere to the fabric surface through intermolecular interactions, while the hydrophilic block favors water interaction, forming a hydration layer between the fabric surface and the aqueous environment. This hydration layer may prevent molecular adhesion to the fiber surface.…”
mentioning
confidence: 99%